2010
DOI: 10.1001/archpediatrics.2010.128
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide in Acute Respiratory Syncytial Virus Bronchiolitis

Abstract: To investigate fractional exhaled nitric oxide (FeNO) levels in infants during acute respiratory syncytial virus (RSV) bronchiolitis and during convalescence.Design: Prospective cohort study. Comparison of FeNO levels between infants with laboratory-confirmed acute RSV bronchiolitis and 2 control groups: healthy infants and infants with recurrent wheezing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
(114 reference statements)
3
28
1
Order By: Relevance
“…He found lower FENO values in the acute phase of bronchiolitis with respect to the other groups. 16 Gadish et al 17 obtained the same results. They measured fractional FENO levels in infants during acute respiratory syncytial virus (RSV) bronchiolitis and during convalescence, and their study shows that FENO levels during acute RSV bronchiolitis are significantly decreased and levels increase back to normal levels and beyond during convalescence.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…He found lower FENO values in the acute phase of bronchiolitis with respect to the other groups. 16 Gadish et al 17 obtained the same results. They measured fractional FENO levels in infants during acute respiratory syncytial virus (RSV) bronchiolitis and during convalescence, and their study shows that FENO levels during acute RSV bronchiolitis are significantly decreased and levels increase back to normal levels and beyond during convalescence.…”
Section: Discussionmentioning
confidence: 54%
“…25 The consistency of these data is limited by the absence of statistical significance that we mainly attribute to the lack of sample. This sample based on previous similar studies 3,17 was insufficient to determine significant differences but it does show a clear trend in the FENO values. After analyzing the results, we calculated the sample size that would be necessary to determine statistical significance with this study design, and we would need 42 patients in each group (alpha error level 5%, beta error level 20%).…”
mentioning
confidence: 99%
“…11 Caution should be used when assessing FeNO levels in children with respiratory tract infections because FeNO levels have been shown to vary by phase of the infection and to be different between studies. 15,16 Medications, including inhaled or systemic corticosteroids or leukotriene receptor antagonists, need to be considered as they significantly reduce FeNO levels. 17,18 Serial measurements should be performed at approximately the same time of the day since circadian rhythms may affect FeNO levels.…”
Section: Subject-related Factorsmentioning
confidence: 99%
“…The study of Tsutsumi et al (1999) revealed that in spite the up-regulation of the Inducible Nitric Oxide Synthase (iNOS) in RSV-infected respiratory epithelial cells, NO production specific for RSV infection itself could not be detected by nitrite assay. Moreover, Gadish et al (2010) investigated the Fractional exhaled Nitric Oxide (FeNO) levels in infants during acute RSV bronchiolitis and during convalescence. They found that the FeNO levels were temporarily reduced during acute RSV bronchiolitis and increased during convalescence to normal levels and higher.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular diastolic function was assessed by measuring mitral E/A ratio where E and A denote early and late mitral flow, respectively. Systolic left ventricular function was assessed by determining the Fractional Shortening (FS) and Ejection Fraction (EF) (Gadish et al, 2010). Interpretations of these studies were performed an attending cardiologist blinded as to the cTp I and miRNAs results.…”
Section: Echocardiographic Studiesmentioning
confidence: 99%